Fabrication of nanoscale NiO/Ni heterostructures as electrocatalysts for efficient methanol oxidation. Issue 20 (10th May 2017) - Wang, Juan; Teschner, Detre; Yao, Yuanying; Huang, Xing; Willinger, Marc; Shao, Lidong; Schlögl, Robert
Abstract : The fabrication of Ni-based heterostructures with controllable compositions (NiO/Ni, NiO and Ni) and structures (core–shell, NiO void shell, Ni core) on oxygen functionalized carbon nanotubes for effective methanol oxidation. Abstract : Nanoscale NiO/Ni heterostructures on oxygen-functionalized carbon nanotubes with low Ni loading (3–4 wt%) are fabricated by delicate thermal-annealing treatments, which are designed according to the temperature-programmed thermal analysis. Activity and stability tests demonstrate that NiO/Ni heterostructures with a stable Ni core inside an oxyhydroxide shell (in solution) exhibit enhanced stability and catalytic activity for methanol oxidation.